1951
DOI: 10.2307/1969490
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of the Static Potential Schrodinger Equation over E n

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1959
1959
1995
1995

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…In the case where a(x, D) is the Laplace operator, Brownell [3] has shown that the fundamental singularity has exponential decay in R n . Next, we need a Green's function G R (τ, z, x) for the bounded cut off domain E R = {xe E: \x | < R}.…”
Section: π {/ G L 2 (E): A(x D)f E L 2 (E)} Tf=a(xd)f Fe^(t)mentioning
confidence: 99%
“…In the case where a(x, D) is the Laplace operator, Brownell [3] has shown that the fundamental singularity has exponential decay in R n . Next, we need a Green's function G R (τ, z, x) for the bounded cut off domain E R = {xe E: \x | < R}.…”
Section: π {/ G L 2 (E): A(x D)f E L 2 (E)} Tf=a(xd)f Fe^(t)mentioning
confidence: 99%
“…Now consider the following condition on V. As stated in Corollary T.4 immediately thereafter, this condition is implied by Condition I, as we see from (15) 2 We note here that ^ need not be dense in L 2 (R n ) if n<3, although H x will not be a very respectable operator from the Hubert space viewpoint if ^ is not dense, in particular not being symmetric. This theorem is the same as our earlier one ( [1]), Theorem 5.3, p. 572) except for change in the initial domain from S^ = ^/^Π ^ there to ^ = ^fΐΊ ĥ ere. Merely sketching the proof, we first see…”
Section: H U](x) = -Y*u{χ) + V(x)u(x)mentioning
confidence: 55%
“…follows for φ e ^ and u e L λ (R n ) Π L 2 (R n ), the proof being unchanged from the earlier one ( [1], Theorem 5.1, p. 568) for φ having continuous second partials and vanishing outside a bounded set. Taking φ e J^ = <Λ" Π Si in (24) and using the facts that G ω is bounded Hermitian and that Since (19) and (16) follow from Condition I for large ω by Theorem T.3, this theorem follows from our earlier one ( [1], Theorem 6.4, p. 579).…”
Section: H U](x) = -Y*u{χ) + V(x)u(x)mentioning
confidence: 81%
See 2 more Smart Citations